2006
DOI: 10.1371/journal.pone.0000135
|View full text |Cite
|
Sign up to set email alerts
|

DNA Encoding an HIV-1 Gag/Human Lysosome-Associated Membrane Protein-1 Chimera Elicits a Broad Cellular and Humoral Immune Response in Rhesus Macaques

Abstract: Previous studies of HIV-1 p55Gag immunization of mice have demonstrated the usefulness of targeting antigens to the cellular compartment containing the major histocompatibility complex type II (MHC II) complex molecules by use of a DNA antigen formulation encoding Gag as a chimera with the mouse lysosome-associated membrane protein (mLAMP/gag). In the present study, we have analyzed the magnitude and breadth of Gag-specific T-lymphocyte and antibody responses elicited in Rhesus macaques after immunization with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 42 publications
2
26
0
6
Order By: Relevance
“…We have demonstrated that association of HIV-1-p55gag (gag, group-specific antigen) with lysosomeassociated membrane protein (LAMP)-1, in the form of naked DNA vaccine (LAMP/gag vaccine) targeted Gag to major histocompatability complex (MHC) II compartments and elicited a diverse, prolonged, and more potent immune response, in mouse and primate experimental models, in comparison to native gag (gag N ) (30)(31)(32)(33)(34). Indeed, immunization with different gag-based DNA vaccines has been shown to induce specific immune response in experimental models (35); however, DNA alone has also shown low immunogenicity in human trials (36).…”
Section: Aids Progression Is Characterized By Depletion and Functionamentioning
confidence: 99%
“…We have demonstrated that association of HIV-1-p55gag (gag, group-specific antigen) with lysosomeassociated membrane protein (LAMP)-1, in the form of naked DNA vaccine (LAMP/gag vaccine) targeted Gag to major histocompatability complex (MHC) II compartments and elicited a diverse, prolonged, and more potent immune response, in mouse and primate experimental models, in comparison to native gag (gag N ) (30)(31)(32)(33)(34). Indeed, immunization with different gag-based DNA vaccines has been shown to induce specific immune response in experimental models (35); however, DNA alone has also shown low immunogenicity in human trials (36).…”
Section: Aids Progression Is Characterized By Depletion and Functionamentioning
confidence: 99%
“…A ativação de células T CD4+ por apresentação de antígenos através de moléculas de classe II do MHC é vital para a função de vacinas genéticas, como demonstrado em camundongos deficientes para moléculas de classe II do MHC ou depletados de células T CD4+ (Chan et al, 2001;Maecker et al 1998 (Chen et al, 2000;Rowell et al, 1995;Ruff et al, 1997). Alguns estudos foram realizados com vacinas quiméricas de DNA, constituídas pelo gene que codifica a LAMP-1, que direciona o tráfego do antígeno para os compartimentos de classe II do MHC, conjugado aos genes de microrganismos como do Plasmodium sp (Dobaño et al, 2007); vírus da dengue , do vírus do papiloma humano (Peng et al, 2005;Chen et al, 2000;Wu et al, 1995) e do HIV-1 (Rowell et al, 1995;Ruff et al, 1997;Marques et al, 2003;De Arruda et al, 2004;Chikhlikar et al, 2004;De Arruda et al, 2006;Chikhlikar et al, 2006).…”
Section: Infectam (Unaids 2008)unclassified
“…Foi demonstrado que a depleção de células CD4+ estimuladas com p55Gag de camundongos adultos imunizados com LAMP/gag diminui a produção de IFN-γ (Marques et al, 2003). De Arruda et al (2006) demonstraram que a vacina LAMP/gag promove aumento na diversidade de epítopos que são reconhecidos pelas células T de camundongos imunizados com a vacina quimérica provavelmente devido ao direcionamento distinto que as proteínas LAMP/gag e Gag seguem no interior das células transfectadas (De Arruda et al, 2006). Ainda, foi observado que a vacina de DNA LAMP/gag aumenta o número de epítopos reconhecidos por células B por um provável aumento na produção da proteína que é produzida e/ou pela alteração da conformação da proteína Gag quando quimerizada com a LAMP-1 (De Arruda et al, 2006).…”
Section: Infectam (Unaids 2008)unclassified
See 2 more Smart Citations